2021
DOI: 10.3390/ijms22126557
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Reveals Roles of Lignin-Modifying Enzymes and Abscisic Acid in the Symbiosis of Mycena and Gastrodia elata

Abstract: Gastrodia elata is a well-known medicinal and heterotrophic orchid. Its germination, limited by the impermeability of seed coat lignin and inhibition by abscisic acid (ABA), is triggered by symbiosis with fungi such as Mycena spp. However, the molecular mechanisms of lignin degradation by Mycena and ABA biosynthesis and signaling in G. elata remain unclear. In order to gain insights into these two processes, this study analyzed the transcriptomes of these organisms during their dynamic symbiosis. Among the 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 74 publications
(79 reference statements)
0
7
0
Order By: Relevance
“…Once symbiosis is established, G. elata begins to grow with increased biological activity, while the fungi are restricted ( Fan et al., 1999a ). Ren et al. (2021) showed this through comparative transcriptome analysis of seed symbiotic Mycena hyphae and pure cultured hyphae, and furthermore, they sequenced and analyzed the genome of Mycena and found that 5024 genes were annotated in the pathogen-host interactions database, among which more than half were linked to reduced virulence and loss of pathogenicity.…”
Section: Mechanism Of Interaction Between Symbiotic Fungi and ...mentioning
confidence: 99%
See 3 more Smart Citations
“…Once symbiosis is established, G. elata begins to grow with increased biological activity, while the fungi are restricted ( Fan et al., 1999a ). Ren et al. (2021) showed this through comparative transcriptome analysis of seed symbiotic Mycena hyphae and pure cultured hyphae, and furthermore, they sequenced and analyzed the genome of Mycena and found that 5024 genes were annotated in the pathogen-host interactions database, among which more than half were linked to reduced virulence and loss of pathogenicity.…”
Section: Mechanism Of Interaction Between Symbiotic Fungi and ...mentioning
confidence: 99%
“…Manganese peroxidase is a fungal lignin-modifying enzyme, and when Mycena breaks through the seed coats of G. elata , manganese peroxidase and laccase are responsible for the degradation of lignin ( Manavalan et al., 2015 ). Ren et al. (2021) conducted transcriptome analysis and found that the upregulation of manganese-dependent peroxidase short genes was conducive to the invasion of G. elata seeds by hyphae.…”
Section: Mechanism Of Interaction Between Symbiotic Fungi and ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, on a model of Gastrodia elata (Epidendroideae) and Mycena sp. signi cant up-regulation of fungal lignin-degrading enzyme genes during OM formation is shown (Ren et al 2021).…”
Section: Introductionmentioning
confidence: 99%